Nexus Between Development and Political System: Evidence from Lebanon - Jassem Ajaka; Hassan Ayoub; Wadad Saad (Journal of Developing Economies, 2026)
Objective: This study examines the interrelationships among three fundamental spheres in Lebanon: the economic sphere, measured by economic growth; the political sphere, reflected in political stability and control of corruption; and the social sphere, measured by human development. Methods: Using a World Bank annual dataset from 1996 – 2019, the study employs four autoregressive distributed lag (ARDL) models that include the following variables: economic growth, political stability, control of corruption, and the Human Development Index (HDI). Each variable is considered as a dependent variable in a model that is regressed on the other remaining variables. Findings: Empirical results reveal that the dynamic interaction between these three spheres exists in the long run and the short run. These findings demonstrate how the variables examined in this study contribute to understanding the underlying mechanisms and policy effects relevant to the research question. Originality/Value: By examining the interrelationships among the three spheres (economic, political, and social spheres) within the Lebanese context, this study addresses an important gap in the literature on the Lebanese economy. Its findings offer policy-relevant insights and contribute to the broader discussion on the design of effective economic policy in Lebanon. Policy Implication: These findings indicate that initiating a developing process at the economic, political, and social levels is a necessary step that the Lebanese authorities must take to overcome the crises that Lebanon has suffered from for decades.